The feasibility of the health insurance projects in Iraq (Global Scientific Review, 2023)
The aim of the research is to delve into the contents of health insurance and determine its importance, foundations and positive impact on the health sector. It provides a financial vision and integrated feasibility for health insurance companies and health service companies, by calculating the break-even point and expected profits of companies. It has used the descriptive approach (a questionnaire form) and the quantitative approach through (financial indicators based on official statistics).